Genetic Polymorphism in TNF-α Promoter Region: Its Association with Severity and Susceptibility to Rheumatoid Arthritis in Iraqi Patients with Active Disease - abdulameer, khalid abdulhussein; Hashim, Zainab (Iraqi Journal of Pharmaceutical Sciences, 2023)
Objectives: To study the prevalence of rs1799964 (-1031 T/C) and rs361525 (- 238 G/A) SNPs and their effect on the disease activity, severity, and cytokines production in newly diagnosed Iraqi rheumatoid arthritis patients.Patients and Methods: sixty-three patients were diagnosed by a specialist physician while attending the rheumatology unit and twenty control participated. The inflammatory markers were measured and PCR amplification and sequencing were performed to demonstrate TNF-α SNPs.Results: Regarding (-1031 C/T) SNP, the TT genotype and allele C were significantly present in the controls, and the CT genotype was distributed significantly in the patients. The TT genotype was mostly distributed in the mild-moderate group, while the CT genotype and allele C were significantly distributed in the severe group. DAS28, TNF-α, IL-1, and ACPA were significantly associated with this SNP. While non-significant differences appeared in the analysis of -238 G/A SNP.Conclusion: The presence of the CT genotype and C allele of) -1031 C/T( was associated with susceptibility to RA. While the CT genotype and C allele were associated with more severe disease. Also, TT genotype was associated with less severe disease. Furthermore, an association between -1031 C/T and the inflammatory markers and DAS28 was reported.